Correlation between the mobility of spin-labeled peptide chains and resin solvation: An approach to optimize the synthesis of aggregating sequences - Cilli, Eduardo Maffud [UNESP]; Marchetto, Reinaldo [UNESP]; Schreier, S.; Nakaie, C. R. (Amer Chemical Soc, 1999)
Resin solvation properties affect the efficiency of the coupling reactions in solid-phase peptide synthesis. Here we report a novel approach to evaluate resin solvation properties, making use of spin label electron paramagnetic resonance (EPR) spectroscopy. The aggregating VVLGAAIV and ING sequences were assembled in benzhydrylamine-resin with different amino group contents (up to 2.6 mmol/g) to examine the extent of chain association within the beads. These model peptidyl-resins were first labeled at their N-terminus with the amino acid spin label 2,2,6,6-tetramethylpiperidine-N-oxyl-4-amino-4-carboxylic acid (Toac). Their solvation properties in different solvents were estimated, either by bead swelling measurement or by assessing the dynamics of their polymeric matrixes through the analysis of Toac EPR spectra, and were correlated with the yield of the acylation reaction. In most cases the coupling rate was found to depend on bead swelling. Comparatively, the EPR approach was more effective. Line shape analysis allowed the detection of more than one peptide chain population, which influenced the reaction. The results demonstrated the unique potential of EPR spectroscopy not only for improving the yield of peptide synthesis, even in challenging conditions, but also for other relevant polymer-supported methodologies in chemistry and biology.